APPLICATION-ORIENTED REVIEW ON LANGUAGE LEARNING STRATEGIES - Lismay, Leli (JR-ELT (Journal of Research in English Language Teaching), 2025)
Language learning strategies (LLS) have been central to second language acquisition research and pedagogy for nearly five decades. Building on seminal studies of “good language learners”(Rubin, 1975; Stern, 1975) and subsequent taxonomies (O’Malley & Chamot, 1990; Oxford, 1990), recent scholarship has explored their role in promoting autonomy, self-regulation, and effective language learning in diverse contexts. This paper provides an application-oriented review on LLS, highlighting theoretical foundations, classroom practices, and new directions in technology-enhanced and English-medium Instruction (EMI) settings. Emphasis is placed on how teachers  can scaffold strategy instruction, how learners can develop autonomy, and how emerging technologies such as mobile learning and AI-powered platforms are reshaping the strategy landscape. The review concludes with recommendations for integrating LLS research into pedagogy, curriculum design, and professional development.